PEMANFAATAN SERBUK GERGAJI JEUNGJING SEBAGAI KOMPOS UNTUK PUPUK TANAMAN - Ridwan Achmad Pasaribu (Jurnal Penelitian Hasil Hutan, 1987)
The result of composting  experiment for the manufacture  of compost  as fertilizer  is reported in this paper. The compost was prepared from jeungjing  (Albizia  falcataria   L. Fosberg)  sawdust  and  rice straw  using  the  indoors  process.  Jeungjing  sawdust  mixed  with  rice straw  were composted  for  10 days, 20 days, 35 days and 55 days. The results are as follows:Except for C/N ratio, the compost produced from different  compositions  of jeungjing  sawdust and rice straw, contained  organic carbon,  total nitrogen  and volume  reduction  of compost  which were not significantly  different. Organic carbon, total nitrogen, C/N-ratio and volume reduction of compost were significantly  affected  by composting time. A combination of 60 percent jeungjing sawdust and 40 percent rice straw composted for about 35 days, produces  compost  with a relatively low C/N ratio (about 45.87) and volume  reduction  of  15.47%  The  C/N  ratio  content   was not  as good  as that  of  soils  which  is about  20 (Thompson, 1957).